Social Media Visual Marketing Strategy for MSMEs Based on Manager Skills Analysis - Salsabila, Puteri; Ciptandi, Faja; Utami, Lira Anindita (Borong Newinera Publisher, 2026)
Despite the advantages offered by digital platforms, fashion MSMEs in the southern part of Bengkulu are still struggling with the adoption of social media for visual marketing, creating a new demand for their businesses.The use of social media for visual marketing is still a challenge for fashion MSMEs in South Bengkulu, even though digital platforms offer a great opportunity for expanding market reach and improving customer engagement. The issue is not the availability of social media platforms, but rather limited visual, technical and strategic skills of the managers of MSME in creating and managing good digital content. The purpose of this study is to find the visual marketing competence level of the managers of fashion MSMEs and to create an effective stage by stage approach that is appropriate to their current competence and business environment. The data collection was carried out using a qualitative approach with the social media observation method, in-depth interviews with MSME managers and consumers in Pasar Manna District, amounting to 74 MSME and 8 consumers, and literature study. The results indicated that majority of MSME managers are at Level 1, which involves basic use of social media, less quality of product photos, lack of information about the business and its products, infrequent posting, poor quality of captions, and inadequate customer interaction. Consumer interviews suggest that clear product pictures, full information, and a responsive communication have a significant impact on the level of consumer trust and purchase interest, whereas manager interviews highlight issues such as limited knowledge, time, cost and mentoring availability.